PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KUALITAS LAPORAN KEUANGAN KAB. MAJALENGKA (Studi Pada Organisasi Perangkat Daerah Kab. Majalengka) - Raden Wulan Saparinda; Mochamad Febri Sayidil Umam; Merlina (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Majalengka Regency received an unqualified opinion for 8 consecutive years from 2013-2020. The purpose of this study is to determine the influence of human resource competence and the application of Government Accounting Standards to the Quality of Financial Statements either partially or simultaneously.The population in this study were employees of the Organisasi Perangkat Daerah (OPD) Majalengka Regency. The sample used in this study were 64 people with data source obtained through the result of filling out a questionnaire. The sampling technique used is purposive sampling. Data analysis used used multiple linear regression with the help of SPSS 23 software.Based on the result of the research conducted, it can be seen that Human Resource Competence and Implementation of Government Accounting Standars have a significant effect on the Quality of Finansial Statements, either partially or simultaneously.